Maximum Ride : the manga. 2 - Lee, NaRae; Patterson, James, 1947-; Patterson, James, 1947- (London : Arrow Books, 2009)
Max and her flock escape the school after recovering Angel, who shares what she has learned about their true identities, but Erasers follow them to New York, where Max ponders her destiny.
Based on: Maximum ride / James Patterson.
Young Adult.
Young Adult
Keywords: Patterson, James, -- 1947- -- Adaptations -- Juvenile literature; Patterson, James, -- 1947- -- Adaptations; Patterson, James, -- 1947- -- Adaptations; Genetic engineering -- Comic books, strips, etc -- Juvenile fiction; Good and evil -- Comic books, strips, etc -- Juvenile fiction; Scientists -- Comic books, strips, etc -- Juvenile fiction; Adventure and adventurers -- Fiction; Cartoons and comics; Genetic engineering -- Fiction; Good and evil -- Fiction; Science fiction; Scientists -- Fiction; Adventure graphic novels; Comic books, strips, etc; Genetic engineering -- Comic books, strips, etc -- Fiction; Good and evil -- Comic books, strips, etc -- Fiction; Graphic novels; Manga; Science fiction graphic novels; Scientists -- Comic books, strips, etc -- Fiction; Adventure fiction; Graphic novels; Science fiction comic books, strips, etc